"Apartheid in a parka"? Roots and longevity of the Canada–South Africa comparison. Issue 4 (1st October 2016) - Horwitz, Simonne
Abstract: Comparisons between Aboriginal policy in Canada and apartheid in South Africa appear frequently in public discourse, often with claims of actual links between the two systems. This paper interrogates these supposed links, using an analysis of land policy and the pass system in each country to demonstrate the improbability of the claims of direct influences. The paper then goes on to analyze the intellectual history of these comparisons, asking why they have been, and continue to be, made by many different actors in the face of a lack of historical evidence. The paper argues that the claims have served the needs of many different groups in different ways and thus maintained a hold despite their lack of historical foundation. However, good policy must be founded on clear analysis of history, and this paper argues that it is important to de-link South Africa and Canada, and understand oppression in each context on its own terms.